Pelatihan Business Model Canvas Pada Entrepreneur Muda Binaan Disporapar Jawa Tengah - Ramadhan, Muhammad Syah Fibrika (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2024)
The Business Model Canvas (BMC) training by the Department of Youth, Sports, and Tourism (Disporapar) of Central Java aims to support and empower young entrepreneurs. This study evaluates the effectiveness of BMC training in enhancing participants' understanding and skills in designing innovative and sustainable business models. The training method includes lectures and hands-on practice, where participants create and present their BMCs. The results show significant improvement in understanding BMC concepts, business analysis, strategy skills, and participants' communication skills. The training also encourages collaboration and networking among participants. In conclusion, BMC training positively impacts participants' business development. Recommendations include extending the training duration, providing supporting materials, and implementing follow-up and mentoring for program sustainability. Keywords: Business Model Canvas, Training, Young Entrepreneurs, Disporapar Central Java, Business Development